Astrocytic Glutamate Transporter 1 (GLT1) Deficiency Reduces Anxiety- and Depression-Like Behaviors in Mice - Jia, Yun-Fang; Wininger, Katheryn; Ho, Ada Man-Choi; Peyton, Lee; Baker, Matthew; Choi, Doo-Sup (Frontiers in Behavioral Neuroscience, 2020)
Glutamatergic dysregulation is known to contribute to altered emotional regulation. Astrocytic glutamate transporter 1 (GLT1) is responsible for the majority of glutamate clearance from synapse. However, the role of astrocytic GLT1 in affective processes such as anxiety- and depression-like behavior is not fully understood. Here, we found that astrocytic GLT1 deficient mice entered more frequently, and spent more time in the open arms of elevated plus maze without difference in overall distance travelled in the open field, nor where there any metabolic changes observed in the metabolic chamber compared to wildtype mice. Moreover, mice lacking astrocytic GLT1 exhibited less immobile time and moved greater area in tail suspension test. Similarly, in the forced swim test, they showed less immobile time and moved greater area. In addition, we found that astrocytic GLT1 deficiency reduced freezing responses in the fear contextual and cued tests. Taken together, our findings suggest that astrocytic GLT1 deficiency decreases anxiety and depression-like behaviors.